# 2m(4-3m)=

## Simple and best practice solution for 2m(4-3m)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 2m(4-3m)= equation:

Simplifying
2m(4 + -3m) = 0
(4 * 2m + -3m * 2m) = 0
(8m + -6m2) = 0
Solving
8m + -6m2 = 0
Solving for variable 'm'.
Factor out the Greatest Common Factor (GCF), '2m'.
2m(4 + -3m) = 0
Ignore the factor 2.
Subproblem 1Set the factor 'm' equal to zero and attempt to solve:
Simplifying
m = 0
Solving
m = 0
Move all terms containing m to the left, all other terms to the right.
Simplifying
m = 0
Subproblem 2Set the factor '(4 + -3m)' equal to zero and attempt to solve:
Simplifying
4 + -3m = 0
Solving
4 + -3m = 0
Move all terms containing m to the left, all other terms to the right.
Add '-4' to each side of the equation.
4 + -4 + -3m = 0 + -4
Combine like terms: 4 + -4 = 0
0 + -3m = 0 + -4
-3m = 0 + -4
Combine like terms: 0 + -4 = -4
-3m = -4
Divide each side by '-3'.
m = 1.333333333
Simplifying
m = 1.333333333Solutionm = {0, 1.333333333}`